(untitled) (Journal of Educational Sciences, 2016)
The authors reviewed the history and problems of children’s music schools in Kazakhstan. The study and understanding of the history of music schools in Kazakhstan at the present stage, helps to understand the role played by these schools in the aesthetic, spiritual and moral education of students in the Soviet period. Analysis of archival material, which is presented by the authors, shows that in all regional centers and cities of the country annually opened children’s music school. Organization and expansion of music schools in Kazakhstan, contributed to introduce children to the arts, their all-round development, music education, as well as the preparation of the musical staff and solving the cultural needs of the country in general. It is noteworthy that the majority of children’s music 7-year schools open in rural, branches music schools were organized directly by industrial plants, buildings, state and collective farms, which is not observed in the modern period. The authors of the article presented the archival materials, as well as a table that provides information about the number of children’s music schools and the number of students in them. The authors chart shows that the socio-economic situation of the 90s and the post-Soviet period, helped reduce many extracurricular institutions. This proves once again the socio-economic, political conditionality of education, culture and art. The authors emphasize that the financial and economic difficulties in these years were overcome by reducing the number of institutions for the development of children, and in those years, not only reduced the number of music schools, but also in other extracurricular institutions. In his article, the authors shows that it was in the 90s of the twentieth century services of many extracurricular educational institutions, including music schools, has to be paid. In the new economic conditions tuition was quite high, this has led to what is studied in music schools, children from wealthy families, and children from low-income families do not have that opportunity.